He Effect Of Jigsaw Type Cooperative Learning Model On The Ability To Analyze The Intrinsic Elements Of Short Story Text Builders In Class XI MAS Project Of AL Washliyah University Medan Learning Year 2023-2024 - Hasanah, Miftahul (Sean Institute, 2024)
The purpose of this study was to determine the effect of the jigsaw type cooperative learning model on the ability to analyze the elements of a short story text builder in class XI MAS Project of Al Washliyah University in the academic year 2023-2024. This study used an experimental research design. This research was conducted in class XI at MAS Project Al Washliyah University Medan. There are three classes in class XI. The total population is 30 students. Sampling with simple random sampling technique in sampling. There were 30 students who were selected as samples. The instrument in data collection is multiple choice questions. Data were analyzed using tests. After the data was analyzed, the results of data analysis showed tobserved higher than ttable (13.24 > 2.00) with degree of freedom df = 58 at a significant level α = 0.05. This indicates that Ha is accepted and Ho is rejected. So in conclusion, there is a significant effect of the jigsaw type learning model on the ability to analyze the elements of a short story text builder in class XI Mas Project of Al Washliyah University Medan Academic Year 2023 - 2024.